Effects of photooxidation on membrane integrity in Salix nigra seeds - Roqueiro, Gonzalo (2010)
Background and Aims: Salix nigra seeds are desiccation-tolerant, as are orthodox seeds, although in contrast to other orthodox seeds they lose viability in a few weeks at room temperature. They also differ in that the chloroplasts of the embryo tissues conserve their chlorophyll and endomembranes. The aim of this paper was to investigate the role of chlorophyll in seed deterioration. Methods: Seeds were aged at different light intensities and atmospheric conditions. Mean germination time and normal and total germination were evaluated. The formation of free radicals was assessed using electronic spin resonance spectroscopy, and changes in the fatty acid composition from phospholipids, galactolipids and triglycerides using gas-liquid chromatography. Membrane integrity was studied with electronic spin resonance spin probe techniques, electrolyte leakage and transmission electron microscopy. Key Results: Light and oxygen played an important role in free-radical generation, causing a decrease in normal germination and an increase in mean germination time. Both indices were associated with a decrease in polyunsaturated fatty acids derived from membrane lipids as phospholipids and galactolipids. The detection of damage in thylakoid membranes and an increase in plasmalemma permeability were consistent with the decrease in both types of lipids. Triglycerides remained unchanged. Light-induced damage began in outermost tissues and spread inwards, decreasing normal germination. Conclusions: Salix nigra seeds were very susceptible to photooxidation. The thylakoid membranes appeared to be the first target of the photooxidative process since there were large decreases in galactolipids and both these lipids and the activated chlorophyll are contiguous in the structure of that membrane. Changes in normal germination and mean germination time could be explained by the deteriorative effects of oxidation.